PENGARUH PEMASARAN VIA ONLINE DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK THREE SECOND PADA MAHASISWA FAKULTAS EKONOMI TAHUN 2013-2015 UNIVERSITAS ISLAM MALANG - Khoerul Wahyudin; N. Rachma (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTThis research was aimed to investigate the influence of online marketingand perception of the price to the decision of the purchase of "three second"products in students of the faculty the economic 2013-2015 UNISMA .Thepopulation of this research is all students of the faculty the economic 2013-2015UNISMA. Sample taken by using the method accidental sampling in order toobtain 94 of respondents who qualified in the sample .This research using theprimary data and and multiple regression analysis method.The result of this research shows that the variable of online marketing haspositive and insignificant effect to the decision of the purchase , the variableprice of perception has negative and significant effect to the decision of thepurchase .Simultaneously variable marketing online , and perception of the pricehave significant influence to the decision of the purchase .Keywords:Online Marketing, Perception Of The Price, Decision Of ThePurchase.